Recent advances in T‐cell immunotherapy for haematological malignancies. (29th November 2016) - Rouce, Rayne H.; Sharma, Sandhya; Huynh, Mai; Heslop, Helen E.
Summary: In vitro discoveries have paved the way for bench‐to‐bedside translation in adoptive T cell immunotherapy, resulting in remarkable clinical responses in a variety of haematological malignancies. Adoptively transferred T cells genetically modified to express CD19 CARs have shown great promise, although many unanswered questions regarding how to optimize T‐cell therapies for both safety and efficacy remain. Similarly, T cells that recognize viral or tumour antigens though their native receptors have produced encouraging clinical responses. Honing manufacturing processes will increase the availability of T‐cell products, while combining T‐cell therapies has the ability to increase complete response rates. Lastly, innovative mechanisms to control these therapies may improve safety profiles while genome editing offers the prospect of modulating T‐cell function. This review will focus on recent advances in T‐cell immunotherapy, highlighting both clinical and pre‐clinical advances, as well as exploring what the future holds.